A Rare Occurrence of Isolated Brain Metastases from Gastric Cancer - Manish M. Karamchandani; Tej Ganti; Sunny Jaiswal; Julian K. Wu; Muhammad Wasif Saif (Case Reports in Medicine)
Background. Gastric cancer is the fourth most common cancer worldwide and the second most common cause of cancer-related death. The majority of newly diagnosed gastric cancer cases present either as locally advanced tumor growth or with distant metastases. Case Report. Here, we describe a case of isolated brain metastases in a male patient with gastric cancer. Initially, our patient presented with dysphagia and was diagnosed with gastric cancer after a thorough evaluation. One year after chemotherapy and surgical resection of his gastric cancer, he presented with headaches, nausea, dizziness, and photophobia. Further evaluation of these symptoms led to the discovery of three metastatic brain lesions without evidence of extracranial metastases. Conclusions. Our review of the literature has found that such cases are rare. Additionally, our review of the literature demonstrates the poor outcomes associated with metastatic brain lesions from gastric cancer and highlights the importance of surgical resection in increasing overall survival time.